Misconceptions of Elementary School Teachers in Character Education: A Mixed Methods Study in Indonesia - Nana Suryana; Wahyu Sopandi; Yadi Ruyadi (Postgraduate, University of Mataram, 2025)
Character education is a strategic agenda in Indonesia’s national education system; however, its implementation in elementary schools still faces various challenges. Previous studies have mostly highlighted implementation aspects, while teachers’ misconceptions about character education have not been systematically examined. This study aims to identify the types of misconceptions elementary school teachers hold regarding character education, the factors causing them, and strategies for improvement. The research design employed an explanatory sequential mixed methods approach involving 150 elementary school teachers in Tasikmalaya Regency. Research instruments consisted of a 25-item Likert questionnaire with Cronbach’s Alpha reliability test, complemented by semi-structured interviews. Findings show that 57% of teachers fall into the medium misconception category, 30% high, and 13% low. The main misconceptions are perceiving character education as identical to enforcing discipline, memorizing moral values, and being the sole responsibility of families. The dominant causal factors are the lack of formal training and the dominance of hidden curriculum. These findings emphasize the importance of sustainable teacher capacity-building programs, integrating character values into lesson plans, and school supervision. The limitation of this study lies in its regional scope and focus on teachers’ perspectives, suggesting that future studies should involve students and parents.